PERSEPSI MASYARAKAT TERHADAP LEMBAGA PENDIDIKAN ISLAM DI DESA PENGKOK KEDAWUNG SRAGEN JAWA TENGAH - Farah Muthia (UIN Fatmawati Sukarno Bengkulu, 2019)
This research used descriptive-qualitative approach with data collection techniquws in the form of observation, interview and documentation. From the research that has done, the findings are as follows. First, people’s knowledge of Islamic education and Islamic educational is good enough; seen from many positive responses of informant who see the very impor- tant Islamic education and Islamic for them. Second, by the attitude of the society towards the Islamic educational institutions, cognitively they have understood the importance of Islamic education and Islamic educational institutions, and affectively their response to the development of Islam is also quite good, visible from the awareness to follow the study / assemblies of existing science. Community behavior is getting better so that the number of criminals is reduced and public participation is increasing in religious activities held by religious leaders of Pengkok Village. Third, public interest in non-formal institutions Islamic education is very high; on the contrary, the interest of the community towards the formal institution of Islamic education is still lacking. in demand due to several factors in the fourth conclusion. Fourth, the lack of public interest in the formal institutions of Islamic Education is due to the following factors. (1) educational background, (2) experience, (3) condition of institution, (4) govern- ment policy, and (5) environment of institution management itself